x^2-5x-84=0
Mọi người giúp mình với ạ
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Leftrightarrow\left(x-3\right)\left(x+3\right)+5x\left(x-3\right)=0\\ \Leftrightarrow\left(x-3\right)\left(6x+3\right)=0\\ \Leftrightarrow3\left(x+2\right)\left(x-3\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-2\\x=3\end{matrix}\right.\)
\(\left(3x-1\right)^2.\left(x+5\right)^2=0\)
\(\Rightarrow\left[{}\begin{matrix}3x-1=0\\x+5=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{1}{3}\\x=-5\end{matrix}\right.\)
a: \(\Rightarrow10x^2+9x-\left(10x^2+15x-2x-3\right)=8\)
\(\Leftrightarrow10x^2+9x-10x^2-13x+3=8\)
=>-4x=5
hay x=-5/4
b: \(\Leftrightarrow21x-15x^2-35+25x+15x^2-10x+6x-4-2=0\)
=>42x=41
hay x=41/42
a: =>3x+3=4x-4
=>-x=-7
hay x=7(nhận)
b: (x-1)(x-3)=0
=>x-1=0 hoặc x-3=0
=>x=1 hoặc x=3
c: 2(x-1)+x=0
=>2x-2+x=0
=>3x-2=0
hay x=2/3
a, ĐKXĐ : x ≠ 1 ; x ≠ -1
\(\Rightarrow3\left(x+1\right)=4\left(x-1\right)\)
\(\Leftrightarrow3x+3=4x-4\)
\(\Leftrightarrow-x=-7\)
\(\Leftrightarrow x=7\left(N\right)\)
b,
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=3\end{matrix}\right.\)
c,
\(\Leftrightarrow2x-2+x=0\)
\(\Leftrightarrow3x=2\)
\(\Leftrightarrow x=\dfrac{2}{3}\)
\(a,\Leftrightarrow x=7-4=3\\ b,\Leftrightarrow2x=-18+5=-13\\ \Leftrightarrow x=-\dfrac{13}{2}\\ c,\Leftrightarrow x-21=10\\ \Leftrightarrow x=31\\ d,\Leftrightarrow-12-x+19=0\\ \Leftrightarrow7-x=0\\ \Leftrightarrow x=7\)
a, <=> x=7-4
<=> x=3
b, 2x= -18 +5
<=>2x=-13
<=> x= -13/2
c, <=> x -21=-10
<=> x= -10 +21
<=> x=11
d, <=> -12+19 -x=0
<=> 7-x=0
<=> x=7
\(x^2+2y^2-2xy+4y+3< 0\)
\(\Rightarrow x^2-2xy+y^2+y^2+4y+4-1< 0\)
\(\Rightarrow\left(x^2-2xy+y^2\right)+\left(y^2+4y+4\right)-1< 0\)
\(\Rightarrow\left(x-y\right)^2+\left(y+2\right)^2-1< 0\)
Mà: \(\left\{{}\begin{matrix}\left(x-y\right)^2\ge0\forall x,y\\\left(y+2\right)^2\ge0\forall y\end{matrix}\right.\)
\(\Rightarrow\left(x-y\right)^2+\left(y+2\right)^2-1\ge-1\forall x,y\)
Mặt khác: \(\left(x-y\right)^2+\left(y+2\right)^2-1< 0\)
Dấu "=" xảy ra:
\(\left\{{}\begin{matrix}x-y=0\\y+2=0\end{matrix}\right.\)
\(\Rightarrow x=y=-2\)
Vậy: ....
\(x^2-5x-84=0\)
=> \(x^2-5x=84\)=> x(x-5)=84
=> \(\orbr{\begin{cases}x=84\\x-5=1\Rightarrow x=6\end{cases}}\); \(\orbr{\begin{cases}x=1\\x-5=84\Rightarrow x=89\end{cases}}\)
=> \(\orbr{\begin{cases}x=-84\\x-5=-1\Rightarrow x=4\end{cases}}\); \(\orbr{\begin{cases}x=-1\\x-5=-84\Rightarrow x=-79\end{cases}}\)
vậy x\(\in\)\((\)84, 6, 1, 89, -84, 4, -1, -79)